Cross-sectoral cooperation needed to prepare for Pakistan’s next flood - Nepal, Santosh; Hafeez, Mohsin; Ringler, Claudia (CGIAR System Organization, 2022)
This blog post summarises the online seminar, NEXUS Gains Talk 5.